DYNAMIC STABILITY OF AEROSTAT DRONE - NOOR AZAHAN, AHMAD FAIZ SAFWAN (IRC, 2017)
In the current generation, drone are having lack of extended hovering and flight time capabilities. Applying a drone with an up thrust inflatable structure such an aerostat can increase energy efficiency. The aerostat can enhance the flight time by cutting the battery usage which reduce the energy use by the rotor. However, adding the aerostat to the drone will affect the stability of the drone itself and lead to less control performance. In this project, the effect of aerostat on the drone system will be investigated. The mathematical model of aerostat drone will be validated by comparing the experimental flight data which involve the drone alone and the drone with aerostat. An experiment was conducted to test the results in term of pitch, yaw and roll rate. Equipped with six sensors, Parrot AR.Drone was used to collect the flight data. Using AutoFlight AR Drone 0.2, the drone is controlled. Then, the designed and fabricated aerostat will be attached to the drone. Then, the Aerostat-Drone will be tested in hovering mode and move forward mode to test the stability of the drone. The result of the experiment shows the differences between the drone without the aerostat and aerostat drone. The addition of the aerostat to the drone can reduces the power consumption of the drone by reducing motor rotational speed. However, the buoyant force of the aerostat will decrease by time that can affect the experiment result